Development and Validation of a Novel Tool for Assessing the Environmental Impact of 3D Printing Technologies: A Pharmaceutical Perspective - Souha H. Youssef; Sadikalmahdi Abdella; Sanjay Garg (MDPI AG, 2022)
Technological advancements have created infinite opportunities and rendered our life easier at several fronts. Nonetheless, the environment has suffered the aftermaths of modernization. Ironically, the pharmaceutical industry was found to be a significant contributor to environmental deterioration. To tackle this issue, continuous eco-evaluation of newly introduced technologies is crucial. Three-dimensional printing (3DP) is rapidly establishing its routes in different industries. Interestingly, 3DP is revolutionising the production of pharmaceuticals and is regarded as a promising approach for the fabrication of patient-centric formulations. Despite the increasing applications in the pharmaceutical field, tools that evaluate the environmental impacts of 3DP are lacking. Energy and solvent consumption, waste generation, and disposal are the main associated factors that present major concerns. For the first time, we are proposing a quantitative tool, the index of Greenness Assessment of Printed Pharmaceuticals (iGAPP), that evaluates the greenness of the different 3DP technologies used in the pharmaceutical industry. The tool provides a colour-coded pictogram and a numerical score indicating the overall greenness of the employed printing method. Validation was performed by constructing the greenness profile of selected formulations produced using the different 3DP techniques. This tool is simple to use and indicates the greenness level of the procedures involved, thereby creating an opportunity to modify the processes for more sustainable practices.